ANALYZING TURN-TAKING STRATEGIES AMONG ADULT LEARNERS IN ESL CLASS DISCUSSION - Syed Abdul Rahman, Sharifah; Rahmat, Noor Hanim; Yunos, D Mohd (PEOPLE: International Journal of Social Sciences, 2015)
Small group discussions have been used in many ESL classrooms to encourage learners to use the target language in natural settings. Teachers of English will agree that there are many advantages of group in the classroom. Group discussions offer learners opportunities to practice “real-world language by debating over issues. Furthermore, class discussions enable learners to accept responsibility over their use of the target language. This may put some students at a disadvantage. They do not participate in the discussion not because they have nothing to say, but because they do not use proper turn-taking strategies to join in the discussion. Some learners are better at using their turn –taking strategies while others may end up staying silent. This quantitative study looks into the turn taking strategies employed learners in group discussions. Using a questionnaire as the instruments, findings of this research revealed that female adult learners are more prone to show agreement in class discussions and that different ESL learners use different strategies for different functions in their discussions.